2015
DOI: 10.1177/1524839915623499
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting African American Churches to Participate in Research

Abstract: Physical activity among African Americans (AA) is low; effective intervention strategies are needed. Community-based settings are useful for delivering health-related interventions in racial/ethnic minority communities. This article describes strategies used to recruit churches for participation in a 22-month intervention designed to increase physical activity levels in AA women. Initial recruitment efforts, led by AA study staff, included direct mailers, phone calls, and in-person meetings with church represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…A previously published paper described the process for recruiting and enrolling churches, and participants within churches, into the study. 24 Eligible churches were those that self-identified themselves with congregations that were predominantly African American. Thirty-one churches, representing 30 sites (two churches were combined) were recruited and randomized into the L.A.D.I.E.S.…”
Section: Methodsmentioning
confidence: 99%
“…A previously published paper described the process for recruiting and enrolling churches, and participants within churches, into the study. 24 Eligible churches were those that self-identified themselves with congregations that were predominantly African American. Thirty-one churches, representing 30 sites (two churches were combined) were recruited and randomized into the L.A.D.I.E.S.…”
Section: Methodsmentioning
confidence: 99%
“…Churches required, on average, 3.5 ± 3.0 months of multiple contacts prior to enrollment (range 0 -9 months). 21 During recruitment, 603 women completed pre-screen questionnaires indicating interest in the study; 469 (78%) enrolled in the study (Figure 1). Complete baseline data were available for 417 women (89%), including 151 randomized to the faith-based (n= 10 churches), 140 randomized to the secular (n=10 churches), and 126 randomized to the control (n=10 churches) conditions.…”
Section: Resultsmentioning
confidence: 99%
“…21 Eligible churches self-identified as predominantly serving African American congregants and were willing to accept randomization to either of the three programs. Eligible participants were: 1) female, African American, regular attendees at the church being recruited; 2) aged > 18 years; 3) self-reported low active (ie, achieving < 150 minutes per week of moderate-to-vigorous physical activity); 4) no physical limitations or medical conditions that would be impacted by physical activity; and 5) no plans to move from the area within a two-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Although we had such relationships with some community partners, we had not established them with the church network. Moreover, past research has found that church-based recruitment of African Americans is more successful when recruiters are native to the community and involved with community churches beyond research activities ( 33 ). Therefore, we recommend using community-based participatory research methods to build relationships and ensuring that recruitment staff reflect the diversity of the priority population.…”
Section: Discussionmentioning
confidence: 99%